Study of adsorption potential of cellulose paper for abusable prescription drug analysis: A practical and sustainable approach validated by BAGI and ComplexMoGAPI tools - Torki A. Zughaibi; Ahmed I. Al-Asmari (Green Analytical Chemistry)
This study develops a green and sustainable analytical method using cellulose paper sorptive extraction (CPSE) coupled with gas chromatography-mass spectrometry (GC–MS) to determine dextromethorphan, tramadol, clozapine, and zolpidem (Ambien) in urine. The method involves immersing five 1″ × 1″ cellulose papers in diluted urine (0.5 mL urine diluted to 10 mL) to adsorb the drugs at 250 rpm for 45 min, followed by desorption with 2 mL methanol at 200 rpm for 10 min and subsequent GC–MS analysis. Key parameters, including the number and size of filter papers, elution solvent type and volume, extraction and elution times and speeds, sample pH, and ionic strength, were extensively optimized. Validation according to SWGTOX guidelines demonstrated excellent linearity (0.05–1 µg mL-1, R² > 0.999), high precision (RSD < 11.1 %), and accuracy (85.1–113.6 %). Sensitivity was high, with LODs ranging from 0.010- 0.013 µg mL-1 and LOQs from 0.033 to 0.043 µg mL-1. The method was successfully applied to blind urine samples, confirming its practical utility in forensic toxicology. Greenness assessment using ComplexMoGAPI and practicality evaluation using Blue Applicability Grade Index (BAGI) yielded high scores (81 and 70), underscoring the method's environmental sustainability and fitness for purpose, positioning it as an eco-friendly alternative to conventional extraction methods.